Skip to main content
Solve for x
Tick mark Image
Graph

Similar Problems from Web Search

Share

\left(2x\right)^{2}-9+5x=2\left(x+1\right)-1
Consider \left(2x+3\right)\left(2x-3\right). Multiplication can be transformed into difference of squares using the rule: \left(a-b\right)\left(a+b\right)=a^{2}-b^{2}. Square 3.
2^{2}x^{2}-9+5x=2\left(x+1\right)-1
Expand \left(2x\right)^{2}.
4x^{2}-9+5x=2\left(x+1\right)-1
Calculate 2 to the power of 2 and get 4.
4x^{2}-9+5x=2x+2-1
Use the distributive property to multiply 2 by x+1.
4x^{2}-9+5x=2x+1
Subtract 1 from 2 to get 1.
4x^{2}-9+5x-2x=1
Subtract 2x from both sides.
4x^{2}-9+3x=1
Combine 5x and -2x to get 3x.
4x^{2}-9+3x-1=0
Subtract 1 from both sides.
4x^{2}-10+3x=0
Subtract 1 from -9 to get -10.
4x^{2}+3x-10=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-3±\sqrt{3^{2}-4\times 4\left(-10\right)}}{2\times 4}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 4 for a, 3 for b, and -10 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-3±\sqrt{9-4\times 4\left(-10\right)}}{2\times 4}
Square 3.
x=\frac{-3±\sqrt{9-16\left(-10\right)}}{2\times 4}
Multiply -4 times 4.
x=\frac{-3±\sqrt{9+160}}{2\times 4}
Multiply -16 times -10.
x=\frac{-3±\sqrt{169}}{2\times 4}
Add 9 to 160.
x=\frac{-3±13}{2\times 4}
Take the square root of 169.
x=\frac{-3±13}{8}
Multiply 2 times 4.
x=\frac{10}{8}
Now solve the equation x=\frac{-3±13}{8} when ± is plus. Add -3 to 13.
x=\frac{5}{4}
Reduce the fraction \frac{10}{8} to lowest terms by extracting and canceling out 2.
x=-\frac{16}{8}
Now solve the equation x=\frac{-3±13}{8} when ± is minus. Subtract 13 from -3.
x=-2
Divide -16 by 8.
x=\frac{5}{4} x=-2
The equation is now solved.
\left(2x\right)^{2}-9+5x=2\left(x+1\right)-1
Consider \left(2x+3\right)\left(2x-3\right). Multiplication can be transformed into difference of squares using the rule: \left(a-b\right)\left(a+b\right)=a^{2}-b^{2}. Square 3.
2^{2}x^{2}-9+5x=2\left(x+1\right)-1
Expand \left(2x\right)^{2}.
4x^{2}-9+5x=2\left(x+1\right)-1
Calculate 2 to the power of 2 and get 4.
4x^{2}-9+5x=2x+2-1
Use the distributive property to multiply 2 by x+1.
4x^{2}-9+5x=2x+1
Subtract 1 from 2 to get 1.
4x^{2}-9+5x-2x=1
Subtract 2x from both sides.
4x^{2}-9+3x=1
Combine 5x and -2x to get 3x.
4x^{2}+3x=1+9
Add 9 to both sides.
4x^{2}+3x=10
Add 1 and 9 to get 10.
\frac{4x^{2}+3x}{4}=\frac{10}{4}
Divide both sides by 4.
x^{2}+\frac{3}{4}x=\frac{10}{4}
Dividing by 4 undoes the multiplication by 4.
x^{2}+\frac{3}{4}x=\frac{5}{2}
Reduce the fraction \frac{10}{4} to lowest terms by extracting and canceling out 2.
x^{2}+\frac{3}{4}x+\left(\frac{3}{8}\right)^{2}=\frac{5}{2}+\left(\frac{3}{8}\right)^{2}
Divide \frac{3}{4}, the coefficient of the x term, by 2 to get \frac{3}{8}. Then add the square of \frac{3}{8} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+\frac{3}{4}x+\frac{9}{64}=\frac{5}{2}+\frac{9}{64}
Square \frac{3}{8} by squaring both the numerator and the denominator of the fraction.
x^{2}+\frac{3}{4}x+\frac{9}{64}=\frac{169}{64}
Add \frac{5}{2} to \frac{9}{64} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x+\frac{3}{8}\right)^{2}=\frac{169}{64}
Factor x^{2}+\frac{3}{4}x+\frac{9}{64}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+\frac{3}{8}\right)^{2}}=\sqrt{\frac{169}{64}}
Take the square root of both sides of the equation.
x+\frac{3}{8}=\frac{13}{8} x+\frac{3}{8}=-\frac{13}{8}
Simplify.
x=\frac{5}{4} x=-2
Subtract \frac{3}{8} from both sides of the equation.